Distribution pattern of medial group retropharyngeal lymph nodes and its implication in optimizing clinical target volume in nasopharyngeal carcinoma - Zong, Dan; Jiang, Ning; Kong, Cheng; Wen, Jing; Wang, Li-jun; Guo, Ye-song; Zhang, Lan-fang; He, Xia; Chen, Zhen-zhang; Huang, Sheng-fu (Frontiers in Oncology, 2023)
Purpose This study aimed to determine the diagnostic value of diffusion-weighted imaging (DWI) and to elucidate the clinical characteristics of medial group retropharyngeal lymph nodes (RLNs) based on multi-modal imaging. Also, we intended to explore the feasibility of optimizing the CTV60 boundary based on the characteristics of medial group RLNs. Methods A total of 549 patients with nasopharyngeal carcinoma received magnetic resonance imaging (MRI), DWI, and contrast-enhanced computed tomography (CT) to detect and evaluate clinical characteristics of medial group RLNs. [18F]Fluorodeoxyglucose positron emission tomography/computed tomography was utilized to identify fluorodeoxyglucose uptaking and contrast-enhanced CT to ensure the reliability of CTV optimization during radiotherapy. The DESdC (Drinking, Eating, Swallowing Difficulties, and Coughing while Eating or Drinking) score was utilized to evaluate swallowing disability. Results Fourteen of 549 patients had medial group RLNs with a transverse diameter of 2.0–19.0 mm, which distributed between the upper margin of 1st cervical vertebra (C1) and the upper one-third of C3. Lasso regression and Pearson chi-square test suggested that its occurrence was associated with stage N, bilateral cervical lymph node metastases, especially when the transverse diameter of cervical lymph nodes was > 3 cm. The sensitivity of DWI, T2 STIR, and contrast-enhanced CT was 100%, 57.1%, and 21.4%, respectively. We optimized CTV60 of medial group RLNs from the base of skull to the upper edge of C2 excluding specific cases. For patients with CTV60 optimization, radiation dose and volume of swallowing structures decreased obviously. Based on our radiotherapy strategy on CTV60, acute toxicities of enrolled patients were well tolerated. Ninety-six of 549 patients had scores with DESdC score. Eighty-three patients scored 1, seven patients scored 2, one patient scored 3, and three patients scored 4. The median interval from the onset of symptoms was 72 (4–114) months. The 5-year overall survival, progression-free survival, local recurrence-free survival, and distant metastasis-free survival were 87%, 80%, 93%, and 85%, respectively. None of the patients with regional recurrence happened in the optimized region. Conclusion DWI possesses superiorities in displaying lymph nodes. Based on the low incidence of the medial RLNs, CTV60 of medial group RLNs from the base of skull to the upper edge of C2 is feasible and has dosimetric advantages for protecting swallowing structures.